Enabling High‐Speed Computing with Electromagnetic Pulse Switching. Issue 12 (9th November 2020) - Yakovlev, Alex; Pacheco‐Peña, Victor
Abstract: Communication and transfer of information from one block to another within a system is fundamental for high‐speed and efficient computing. Herein, a simple approach for computing, without using conventional electrical charge/discharge‐based primitive operations, in which information is represented in electromagnetic energy steps travelling in sections of transmission lines, is proposed. These steps are formed by transverse electromagnetic (TEM) square pulses with a polarity representing the values of Boolean variables. Logical operations between variables are realized at the crossing point of inter‐connected transmission lines by exploiting the known laws of reflection and transmission of TEM waves allowing power division and/or recombination. A series and parallel configurations for at‐will square pulse manipulation are discussed, offering new possibilities for future electromagnetic pulse‐based computing systems. Abstract : A simple technique to control simple square transverse electromagnetic (TEM) pulses is proposed using N‐ interconnected transmission lines in a series or parallel configuration. Logical operations for re‐routing/switching the pulses at will are performed demonstrating power division and recombination. Such proposed approach for controlling square‐pulse propagation can be used for future high‐speed computing systems.